Dynamic change of fecal microbiota and metabolomics in a polymicrobial murine sepsis model - Arisa Muratsu; Mitsunori Ikeda; Kentaro Shimizu; Shoichiro Kameoka; Daisuke Motooka; Shota Nakamura; Hisatake Matsumoto; Hiroshi Ogura; Takeshi Shimazu (Acute Medicine & Surgery, 2022)
Aim Sepsis causes a systemic inflammatory reaction by destroying intestinal flora, which leads to a poor prognosis. In this study, we sought to clarify the characteristics of fecal flora and metabolites in a mouse model of sepsis by comprehensive metagenomic and metabolomic analysis. Methods We performed a cecal ligation and puncture model procedure to create a mild sepsis model. We collected fecal samples on day 0 (healthy condition) and days 1 and 7 after the cecal ligation and puncture to determine the microbiome and metabolites. We analyzed fecal flora using 16S rRNA gene sequencing and metabolites using capillary electrophoresis mass spectrometry with time‐of‐flight analysis. Results The abundance of bacteria belonging to the family Enterobacteriaceae significantly increased, but that of order Clostridiales such as the families Lachnospiraceae and Ruminococcaceae decreased on day 1 after the cecal ligation and puncture compared with those before the cecal ligation and puncture. The family Enterobacteriaceae significantly decreased, but that of order Clostridiales such as the families Lachnospiraceae and Ruminococcaceae increased on day 7 compared with those on day 1 after the cecal ligation and puncture. In the fecal metabolome, 313 metabolites were identified. Particularly, essential amino acids such as valine and non‐essential amino acids such as glycine increased remarkably following injury. Betaine and trimethylamine also increased. In contrast, short‐chain fatty acids such as isovaleric acid, butyric acid, and propionic acid decreased. Conclusion The fecal microbiota following injury showed that Enterobacteriaceae increased in acute phase, and Lachnospiraceae and Ruminococcaceae increased in subacute phase. The metabolites revealed an increase in essential amino acids and choline metabolites and a decrease in short‐chain fatty acids.